1997
DOI: 10.1074/jbc.272.11.7320
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of a Novel Murine Cell-surface Glycoprotein Homologous to Killer Cell Inhibitory Receptors

Abstract: We have isolated a cDNA clone encoding a novel murine cell-surface glycoprotein. This polypeptide is predicted to be composed of a signal peptide of 23 amino acids, an extracellular region of 620 amino acids that contains six immunoglobulin-like domains with five potential N-glycosylation sites, a transmembrane sequence of 20 amino acids, and a cytoplasmic tail of 178 amino acids with four sets of sequences similar to the immunoreceptor tyrosine-based inhibition motif. The relative molecular mass of the mature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(104 citation statements)
references
References 43 publications
3
101
0
Order By: Relevance
“…All of the ectodomains, each containing six Ig-like domains, are Ͼ92% identical at the amino acid level (20,21). Therefore, it had been thought that both PIR-B and PIR-A recognize the same ligands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the ectodomains, each containing six Ig-like domains, are Ͼ92% identical at the amino acid level (20,21). Therefore, it had been thought that both PIR-B and PIR-A recognize the same ligands.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that PIR-B has ITIMs in the cytoplasmic region (20,21) suggests that PIR-B does transmit an inhibitory signal in macrophages upon microbial recognition. We demonstrate in this study that upon binding to S. aureus, PIR-B suppresses the TLR-mediated inflammatory response via the anti-inflammatory cytokine IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further genomic studies are necessary to establish whether all of the cloned ILT5 variants are encoded by different alleles at the same locus or by different loci. Human ILT receptors are homologous to murine paired Ig-like receptors (PIRs) [21,27,28] and murine gp49 receptors [29][30][31][32][33]. PIRs are members of the Ig-superfamily characterized by six extracellular Ig-SF domains and by differing transmembrane and cytoplasmic domains.…”
Section: Ilt Receptor Structurementioning
confidence: 99%
“…1 This suggests that it may be important to identify therapeutic strategies that specifically target LSCs while maintaining normal hematopoietic stem cells (HSCs). Previously, Guzman et al reported the activity of a natural compound, parthenolide (PTL), as a potent in vitro agent that selectively affects leukemic initiating cells but not normal progenitors.…”
Section: Targeting Lscs: Powering An Old Tool -----------------------mentioning
confidence: 99%